A case of cirsoid hemangioma of the upper lip - YOSHIDA, Hiroshi; AKIZUKI, Hiromichi; MICHIWAKI, Yukihiro; MICHI, Ken-ichi; WAKUMOTO, Masahiko; YAMANA, Hiromi (Japanese Journal of Oral and Maxillofacial Surgery, 1987)
Cirsoid hemangioma is a rare disease presenting as a pulsating, compressible mass. It grows up rapidly and communicates with surround vessels. It is said that it occurs mainly on the face and neck.However, only few reports on the oral region have been published. A 65-year-old male with the cirsoid hemangioma is presented.He was referred to our hospital with complaint of upper lip swelling.The swelling showed pulsation and compressibility, and had rapidly increased in size from a month before.It was accordingly diagnosed as cirsoid hemangioma. This hemangioma was succesfully treated by surgical excision with upper lip artery ligation. The classification and differentiation of this lesion is discussed.